Modeling premium growth in the Malaysian Motor Insurance Industry - Lee, Tak Chen; Hendon Redzuan; Rasidah Mohd Said; Arawati Agus (Penerbit Universiti Kebangsaan Malaysia, 1994)
The motor insurance industry came into the limelight since the enforcement of mandatory motor insurance coverage in 1959 This paper uses a modeling technique to ascertain the various components and parameters that affect the change in premiums receIved by the entire industry, or a segment of it. Once these components & parameters are identified, the actual growth of new premiums can be derived by extrapolating the components and parameters in one or more expressions (or commonly referred to as a formula). These expressions could be useful in forecasting the future market dynamics of the motor Insurance Industry.